An Approach to the Synthesis of Pyrimido[b]azepines via Ruthenium-Catalyzed Ring-Closing Metathesis - Zhang, Tong-Bo; Yang, Quan-Zhi; Cao, Yuan-Yuan; Wu, Shao-Tong; Zhang, Yu; Guo, Ying; Zhao, Jian-Xiong; Sun, Xue-Feng; Zhang, Zhi-Li; Tian, Chao; Liu, Jun-Yi; Wang, Xiao-Wei (Synthesis, 2015)
A highly efficient approach to the synthesis of a series of pyrimido[b]azepines has been developed with 5-allyl-2,4,6-trichloropyrimidine as the starting material in six or seven steps via a ring-closing metathesis (RCM) reaction. The absolute configuration of the key intermediate pyrimido[4,5-b]azepine was ascertained by X-ray crystal structure analysis.
Keywords: RCM; pyrimido[b]azepines; pyrimido[4,5-b]azepine-2,4-dione; Grubbs catalyst; inhibitors of HIV-1 RT